Relationship Between Physical Activity and Stress Among UNNES Sports Science Students - Muhammmad Ismail Abdul Fatah; Agus Darmawan (Universitas Negeri Semarang, 2026)
Final-semester students are vulnerable to accumulated psychological stress from demanding academic obligations, including final assignments and workforce transition preparation, making stress a serious threat to well-being. Exercise and physical activity have long been known to mitigate this stress through biological and neuropsychological pathways. This study examines the relationship between daily physical activity intensity and psychological well-being among final-semester students at the Faculty of Sport Science. A quantitative correlational design was used, involving 200 respondents selected through random sampling from the Faculty of Sport Science class of 2022. Physical activity was measured using the IPAQ instrument and categorized by MET-minutes/week as low (below 600), medium (600-3000), and high (above 3000), while stress was assessed using the DASS-21, ranging from normal to very high. Data were analyzed using Spearman correlation and Chi-Square tests. Results showed a strong negative correlation between the variables (rs = -0.692; p < 0.001), with strong association strength (Gamma = -0.850; p < 0.001). The distribution of stress categories differed significantly between activity groups (χ² = 117.784; df = 8; p < 0.001). Students with higher physical activity had significantly better psychological well-being, reinforcing the need for active movement promotion strategies as mental health interventions in higher education.